Time-dependent measurements of length and area of the contact line in contact-boiling regime - Mohammad Khavari (2022)
During the impact of a liquid droplet on a sufficiently heated surface, bubble nucleation reduces the contact area between the liquid and the solid surface. Using high-speed imaging combined with total internal reflection, we measure and report how the contact area decreases with time for a wide range of surface temperatures and impact velocities. We also reveal how formation of the observed fingering patterns contributes to a substantial increase in the total length of the contact line surrounding the contact area.